Pengujian Aplikasi Reservasi Hotel di LeGreen Hotel & Suite dengan Metode Black Box Testing Boundary Value Analysis - Yani, Achmad; Setiawan, Deny; Sofian, Novrizal Egi; Subagja, Rizky; Desyani, Teti (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2020)
In this test we will use software that has been made, namely the desktop-based LeGreen Hotel Reservation Application. In testing this hotel room reservation application, the writer uses the black box testing method. Black Box Testing is suitable in testing hotel booking applications because this test aims to ensure the functionality of the LeGreen Hotel Reservation application. This study has several stages that must be done, including the identification of experimental problems, input data samples into the process system, then testing to evaluate the output and finally the documentation of test results. Based on the analysis of the results of the application of methods to solve the problem shows that the level of application that runs reaches 70%, able to run and process employee data, rooms, visitors and payments used for hotel reservations. In the admin login form of 30%, only 20% succeeded, and in the Print Report Form, repairs are needed in order to improve the quality of the application in processing report print data as it functions.